2011
DOI: 10.1186/1471-2148-11-68
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and postmating reproductive isolation between allopatric Drosophila montana populations suggest speciation potential

Abstract: BackgroundWidely distributed species with populations adapted to different environmental conditions can provide valuable opportunities for tracing the onset of reproductive incompatibilities and their role in the speciation process. Drosophila montana, a D. virilis group species found in high latitude boreal forests in Nearctic and Palearctic regions around the globe, could be an excellent model system for studying the early stages of speciation, as a wealth of information concerning this species' ecology, mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…Some Drosophila species from mountainous areas or from colder climates or such species with more extended life cycles (Begon 1976; Keightley 2000; Jennings et al 2011) are known to have fewer generations per year, similar to D. willistoni and the Hawaiian D. grimshawi for which we assumed five generations per year.…”
Section: Methodsmentioning
confidence: 99%
“…Some Drosophila species from mountainous areas or from colder climates or such species with more extended life cycles (Begon 1976; Keightley 2000; Jennings et al 2011) are known to have fewer generations per year, similar to D. willistoni and the Hawaiian D. grimshawi for which we assumed five generations per year.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, TA female fecundity was lower in intra‐population crosses than in inter‐population crosses but without showing a significant difference. It is possible that larger XS males may contain more sperm or can stimulate ovulation and oviposition (Jennings et al ., ). Our experiments also showed that inter‐population crosses (XS female × TA male and TA female × XS male) resulted in significantly lower egg hatching rate and shorter female longevity than intra‐population crosses from both XS and TA populations (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, R. ramosae females mated with males of both species. Sexual selection has been claimed to be one of the most important forces triggering divergence and speciation between populations with allopatric history (Ritchie, 2007;Jennings et al, 2011). Sexual selection has been claimed to be one of the most important forces triggering divergence and speciation between populations with allopatric history (Ritchie, 2007;Jennings et al, 2011).…”
Section: Discussionmentioning
confidence: 99%